The musicbiographyzation as narrative intrigue: a theoretical essay between the (auto)biographic and music education research (Orfeu, 2022)
This article aims to raise the dialectic of music biographization as a narrative intrigue between the field of (auto)biographical research and music education, in an essayistic way. In a philosophy of ipseity, the possession of a notional term – music biographization – is not what matters, but the engendering of the narrative as a dialectic of the between, finding the complicity of this (auto)biographical movement in the area of ​​music education in Brazil. In this Adamic moment, in which we are naming the concepts that dialogue with the field of Autobiographical Research and Music Education, the thesis defended here is that music biographization is understood as delegating to itself the operation of composing these fields of knowledge. The aim is to show how this is inscribed in the poles of permanence between music education and (auto)biographical research, in order to mediate between them, covering the spectrum of meanings from an investigative field to another in which what differs overlaps. and fully associates.
Keywords: Music Education; autobriographic research; musicobiography; narrative intrigue; theoretical essay